Tribological behavior of unfilled PTFE under dynamic loading in dry sliding condition - Kiran Ashokrao Chaudhari; Jayant Hemchandra Bhangale (Journal of Materials Science: Materials in Engineering)
Abstract Polytetrafluoroethylene (PTFE) is widely utilized in engineering applications due to its low friction, self-lubricating properties and chemical inertness. However, its tribological performance under variable loading conditions has been insufficiently studied. This research investigates the influence of variable loading on the wear and friction characteristics of PTFE under dry sliding conditions, particularly within the context of rolling and sliding contact bearings. A modified pin-on-disk tribometer equipped with a variable loading assembly was used to simulate fluctuating load scenarios commonly encountered in bearing applications. The results show that PTFE experiences wear rates that fall between those observed under mean and maximum constant loading conditions, with a notable increase in wear and specific wear rate compared to mean static loads. However, no similar trend was observed for the friction coefficient. These results provide insightful information on the optimization of PTFE performance in dynamic environments including bearings, biomedical implants, and mechanical seals.